1992
DOI: 10.21273/hortsci.27.11.1198
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sucrose in Bud Development and Vase Life of Cut Liatris spicata (L.) Willd.

Abstract: Sucrose addition to the vase solution improved the postharvest qualities of cut liatris by increasing the length of inflorescences showing color and by prolonging the vase life of the spikes. The main effect of sucrose was on the development and opening of the flower heads with minimal effect on their longevity. Pulsing with concentrations of sucrose ≥10% for 20 hours prolonged the vase life of the spikes. Responses of spikes to the pulsed treatment varied greatly due to the differences in their degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 8 publications
1
6
0
1
Order By: Relevance
“…The constant longevity of individual flowers within inflorescences which was observed (Fig. 2B) has also been observed in Liatris (Han, 1992), Gladiolus (Yamane et al, 1993), and Freesia (Spikman, 1989). In Freesia individual flower longevity remained constant even when sucrose was supplied (Spikman, 1989).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The constant longevity of individual flowers within inflorescences which was observed (Fig. 2B) has also been observed in Liatris (Han, 1992), Gladiolus (Yamane et al, 1993), and Freesia (Spikman, 1989). In Freesia individual flower longevity remained constant even when sucrose was supplied (Spikman, 1989).…”
Section: Resultssupporting
confidence: 79%
“…In Freesia individual flower longevity remained constant even when sucrose was supplied (Spikman, 1989). Liatris individual flower heads required sucrose for complete opening, after which longevity was not further influenced by the amount of sucrose supplied (Han, 1992). In both cases, an artificial sugar supply increased the number of floral buds opening and, therefore, longevity of the inflorescence.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The use of sugars to promote flower development and pigmentation is common practice, and most pulsing and holding solutions applied to cut flowers include sucrose (Suc) ( Halevy and Mayak 1981). Increased Suc concentration enhanced petal growth and pigmentation in detached flowers of Eustoma grandiflorum ( Kawabata et al 1995), Hyacinthus orientalis ( Hosokawa et al 1996), Liatris spicata ( Han 1992) and rose ( Kuiper et al 1991). Several studies have shown that sugar level increases during petal development to a maximum at the stage of rapid cell expansion ( Tsukaya et al 1991; Bieleski 1993; Clement et al 1996).…”
Section: The Role Of Sugarsmentioning
confidence: 99%
“…It is well known that sugars prevent senescence of cut flowers and vegetables. Sucrose improved the postharvest life of cut flowers of Limonium (Doi and Reid, 1995), Liatris (Han, 1992), Eustoma grandiflorum (Cho et al, 2001), and many other species. Sucrose supply increased longevity and inhibited chlorophyll degradation of broccoli (Brassica oleracea) branchlets (Irving and Joyce, 1995).…”
Section: Effect Of Soluble Sugars On Chlorophylls and Phenolic Compoumentioning
confidence: 99%